2014
DOI: 10.22470/pemj.2014.1.2.83
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Ondansetron on Vomiting Associated with Intramuscular Ketamine Sedation in Children: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: The purpose of this study is to investigate the effect of oral ondansetron on the incidence of vomiting in children who receive intramuscular (IM) ketamine for procedural sedation and analgesia in the emergency department (ED). Methods: In this double-blind, randomized, placebo-controlled trial in a children's hospital ED, patients receiving IM ketamine (5 mg/kg) for ED procedures were randomized to receive either oral ondansetron (2 mg or 4 mg) or placebo 15 minutes before the ketamine injection. We recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…All five RCTs addressed the question of vomiting in the ED post-PSA (n = 856). Four trials (n = 735) reported the incidence of vomiting post-discharge, three for up to 12 h 16,17,28 and one for up to 24 h. 15 One trial did not report vomiting postdischarge. 29 The age of participants was 4 years (mean) and ranged from 1 to 18 with a female-to-male ratio of 45.3% versus 54.7%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…All five RCTs addressed the question of vomiting in the ED post-PSA (n = 856). Four trials (n = 735) reported the incidence of vomiting post-discharge, three for up to 12 h 16,17,28 and one for up to 24 h. 15 One trial did not report vomiting postdischarge. 29 The age of participants was 4 years (mean) and ranged from 1 to 18 with a female-to-male ratio of 45.3% versus 54.7%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study was published in Korean. 16 All corresponding authors were contacted for clarification on missing information, such as the timing of prophylactic ondansetron and the use of adjunctive medications where relevant. None replied.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations